2018
DOI: 10.1515/aoas-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Red Osier Dogwood in High-Forage and High-Grain Diets Affected in Vitro Rumen Fermentation

Abstract: Red osier dogwood (ROD) is an abundant shrub plant in Canada and other places in the world. It is rich in antioxidants such as quercetin, gallic acid and tyrosol. The objective of this study was to evaluate the effects of substituting barley silage with ROD in high-forage (HF) or high-grain (HG) diets on gas production (GP), dry matter (DM) disappearance (DMD) and fermentation characteristics in ruminal batch cultures. The study was a randomized design with 2 media pH (5.8 vs. 6.5) × 4 doses of ROD. An additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…It is well-established that supplementing feed additives can alter individual VFA profiles and fermentation patterns (5,9). For example, it is well-known that feeding monensin to ruminants increases propionate production and decreases the A:P ratio, thus improving energy efficiency (5). The trend of increased acetate concentration and the A:P ratio due to the addition of the ROD extract to the basal diet in the present study is in agreement with the previous batch culture study (5).…”
Section: Effects Of Rod Extractsupporting
confidence: 91%
See 2 more Smart Citations
“…It is well-established that supplementing feed additives can alter individual VFA profiles and fermentation patterns (5,9). For example, it is well-known that feeding monensin to ruminants increases propionate production and decreases the A:P ratio, thus improving energy efficiency (5). The trend of increased acetate concentration and the A:P ratio due to the addition of the ROD extract to the basal diet in the present study is in agreement with the previous batch culture study (5).…”
Section: Effects Of Rod Extractsupporting
confidence: 91%
“…It is well-established that supplementing feed additives can alter individual VFA profiles and fermentation patterns (5,9). For example, it is well-known that feeding monensin to ruminants increases propionate production and decreases the A:P ratio, thus improving energy efficiency (5).…”
Section: Effects Of Rod Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, it is a precious plant resource and rich in phenolic components, including anthocyanins with strong antioxidative activity [18]. At present, ground red-osier dogwood has been investigated in animal feeds to improve growth performance, feed intake, disease prevention, and meat quality [19,20]. Researchers [19,20] investigated the effects of ground red-osier dogwood supplementation on the digestibility, blood metabolites, and acute phase response in beef heifers.…”
Section: Introductionmentioning
confidence: 99%
“…At present, ground red-osier dogwood has been investigated in animal feeds to improve growth performance, feed intake, disease prevention, and meat quality [19,20]. Researchers [19,20] investigated the effects of ground red-osier dogwood supplementation on the digestibility, blood metabolites, and acute phase response in beef heifers. The results showed that ground red-osier dogwood could increase the feed digestibility and plasma concentration of haptoglobin and serum amyloid A in a ground red-osier dogwood dose-dependence.…”
Section: Introductionmentioning
confidence: 99%